2022
DOI: 10.3390/sym14020312
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Variant of Pollard’s p − 1 for the Case That All Prime Factors of the p − 1 in B-Smooth

Abstract: Due to the computational limitations at present, there is no efficient integer factorization algorithm that can break at least 2048 bits of RSA with strong prime factors in polynomial time. Although Shor’s algorithm based on a quantum computer has been presented, the quantum computer is still in its early stages of the development. As a result, the integer factorization problem (IFP) is a technique that is still being refined. Pollard’s p − 1 is an integer factorization algorithm based on all prime factors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Before RSA was introduced, prior results had shown that p − 1 and q − 1 that have small factors cause p • q to be vulnerable when factored in polynomial time using the Pollard p − 1 algorithm [5]. Pollard's p − 1 algorithm is exceptionally efficient whenever all prime factors of p − 1 and q − 1 are small [6]. In addition, a technique known as an estimated prime factor (EPF) was improved by Tahir et.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before RSA was introduced, prior results had shown that p − 1 and q − 1 that have small factors cause p • q to be vulnerable when factored in polynomial time using the Pollard p − 1 algorithm [5]. Pollard's p − 1 algorithm is exceptionally efficient whenever all prime factors of p − 1 and q − 1 are small [6]. In addition, a technique known as an estimated prime factor (EPF) was improved by Tahir et.…”
Section: Introductionmentioning
confidence: 99%
“…From [24], we know that the classical modular reduction of modulo σ works at O(2 log 2 σ). Since σ is the potential value of (ab) m/2 , the maximum integers to find it are less than N γ 2 m/2 +1 2 , as shown in Equation (6). Based on this computation, we have the complexity of Attack I presented in Algorithm 2 to be…”
mentioning
confidence: 99%
“…Many problems in number theory and computer arithmetic play important roles in cryptography. Examples of such problems are the generation of prime numbers [1][2][3], primality testing [4,5], modular exponentiation [6], addition chains and sequences [7,8] and integer factorization [9][10][11][12]. Developing fast algorithms that address these problems is one of the main challenges of algorithm complexity and leads to significant improvements in various applications.…”
Section: Introductionmentioning
confidence: 99%